A rapid and accurate method for screening T-2 toxin in food and feed using competitive AlphaLISA. Issue 6 (23rd March 2021) - Zhang, Liwen; Lv, Qingyu; Zheng, Yuling; Chen, Xuan; Kong, Decong; Huang, Wenhua; Liu, Peng; Jiang, Hua; Jiang, Yongqiang
ABSTRACT: T-2 is a common mycotoxin contaminating cereal crops. Chronic consumption of food contaminated with T-2 toxin can lead to death, so simple and accurate detection methods in food and feed are necessary. In this paper, we establish a highly sensitive and accurate method for detecting T-2 toxin using AlphaLISA. The system consists of acceptor beads labeled with T-2-bovine serum albumin (BSA), streptavidin-labeled donor beads and biotinylated T-2 antibodies. T-2 in the sample matrix competes with T-2-BSA for antibodies. Adding biotinylated antibodies to the test well followed by T-2 and T-2-BSA acceptor beads yielded a detection range of 0.03–500 ng/mL. The half-maximal inhibitory concentration was 2.28 ng/mL and the coefficient of variation was <10%. In addition, this method had no cross-reaction with other related mycotoxins. This optimized method for extracting T-2 from food and feed samples achieved a recovery rate of approximately 90% in T-2 concentrations as low as 1 ng/mL, better than the performance of a commercial ELISA kit. This competitive AlphaLISA method offers high sensitivity, good specificity, good repeatability and simple operation for detecting T-2 toxin in food and feed. Abstract : A T-2 competitive AlphaLISA homogeneous method was established with high sensitivity, good specificity, good repeatability and simple operation that advances T-2 detection methods.